Agency Cost dan Kebijakan Dividen (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Elliv Hidayatul Lailiyah; Muhammad Dzikri Abadi (Universitas Medan Area, 2021)
Manufacturing companies in Indonesia are large-scale companies and dominate the Indonesia Stock Exchange. The number of companies listed on the stock exchange is increase every year, which results in more people having the opportunity to own a company. The spread of more investors who own the company makes conflict between owners even higher. The purpose of this study is to determine the effect of agency cost proxied by insider ownership, dispersion of ownership, free cash flow, and collateralizable assets on dividend policies of manufacturing companies in Indonesia. Data in the form of secondary data in the form of financial reports and annual reports for the period 2012-2019. The data used multiple linear regression statistical analysis techniques. The results of this study show that agency cost, which is proxied by dispersion ownership, free cash flow and collateralizable assets, has a positive effect on dividend policy. A firm in its operational activities, carries out agency relationships. Agency problems arise when an agent acts not in accordance with the principal's interests, which causes a conflict of interest between the principal and agent. Agency problems will increase agency cost. The agency problem can be reduced by the dividend payment mechanism, namely by increasing the proportion of dividend payments from company profits for stockholders. In contrast to insider ownership which does not affect dividend decisions because the percentage of company ownership owned by insiders is limited in Indonesia.